Need Analysis to Create Heat E-Module with Problem Based Learning Model Asisted Heyzine Application to Promote Student’s Critical Thinking Skills - Muhammad Surya Meliano; Dea Stivani Suherman; Ratnawulan Ratnawulan; Fauziah Ulmi (Journal of Innovative Physics Teaching, 2026)
The ideal condition of 21st-century physics learning is the implementation of interactive, student-centered learning that integrates technology and innovative learning models to develop students’ critical thinking skills. However, the results of the needs analysis conducted at SMA Negeri 14 Padang indicate several problems. First, students’ critical thinking skills are still in the very low category, with an average score of 40. Second, the teaching materials used in schools have not fully supported 21st-century learning, particularly in the visual and multimedia aspects (40) and adaptive aspect (46.67). Third, the integration of the Problem Based Learning model in teaching materials is still not optimal, especially in the aspects of developing and presenting work (30) and analyzing and evaluating the problem-solving process (40). Fourth, students’ mastery of physics concepts is still relatively low, with an average score of 43.8. In addition, the analysis of student characteristics indicates that students have positive responses toward technology-based learning. These findings indicate the need to develop a Problem Based Learning-based e-module assisted by the Heyzine application. The developed e-module is expected to provide more interactive, adaptive, and meaningful learning experiences while facilitating the improvement of students’ critical thinking skills and conceptual understanding in heat learning.